2013
DOI: 10.1074/jbc.m113.488866
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β1 Inhibits Trophoblast Cell Invasion by Inducing Snail-mediated Down-regulation of Vascular Endothelial-cadherin Protein

Abstract: Background: Transforming growth factor (TGF)-␤1 treatment decreases human trophoblast invasion. Results: Smad-dependent up-regulation of Snail mediates TGF-␤1-induced down-regulation of VE-cadherin. Conclusion: TGF-␤1 decreases human trophoblast invasion by down-regulating VE-cadherin. Significance: Our results provide important insights into the molecular mechanisms mediating TGF-␤1-induced down-regulation of VE-cadherin and decreased cell invasion in human trophoblast cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 51 publications
(61 reference statements)
3
76
0
3
Order By: Relevance
“…4C). Prolonged treatment with TGF-␤ alone was sufficient for Snail up-regulation and the induction of EMT, but it could not increase the number of CD44 high /CD24 low cells or Twist expression even in combination with TNF-␣, which was consistent with an earlier observation that TGF-␤ treatment minimally affects Twist expression (31,32).…”
Section: Involvement Of Tgf-␤/tnf-␣ Signaling Pathways In Has2-supporting
confidence: 80%
“…4C). Prolonged treatment with TGF-␤ alone was sufficient for Snail up-regulation and the induction of EMT, but it could not increase the number of CD44 high /CD24 low cells or Twist expression even in combination with TNF-␣, which was consistent with an earlier observation that TGF-␤ treatment minimally affects Twist expression (31,32).…”
Section: Involvement Of Tgf-␤/tnf-␣ Signaling Pathways In Has2-supporting
confidence: 80%
“…In vitro studies demonstrate that TGFb1 increases the expression of E-cadherin, 30 a feature of cells in the epithelial state. TGFb1 also acts through 2 key transcriptional regulators of EMT in trophoblast cells; SNAIL 25 and TWIST, 33 which are discussed in the next section.…”
Section: Inducers Of Emtmentioning
confidence: 99%
“…TGFb plays crucial roles in regulating trophoblast cell adhesion, proliferation, differentiation, migration and invasion at the maternal-fetal interface. [25][26][27][28][29][30] TGFb exists in 3 different isoforms, with TGFb1 and TGFb2 thought to be the most important at the maternal-fetal interface. EVTs within the placental bed express TGFb2, while extracellular TGFb1 and cytoplasmic TGFb2 are localized within the decidua.…”
Section: Inducers Of Emtmentioning
confidence: 99%
“…The results of our study also confirmed that the TGF-β1-stimulated phosphorylation of Smad2/Smad3 had an influence on the EndMT in HCAECs. Snail and Slug are critical EndMT inducers, which allow the acquisition of mesenchymal phenotype through the regulation of several proteins related to EndMT, such as regressing VE-cadherin and E-cadherin, which are essential for endothelial cell-to-cell adhesion [30]. In addition, the TGF-β1/Smad signaling pathway has been found to be associated with plaque formation and rupture [31].…”
Section: Discussionmentioning
confidence: 99%